2017
DOI: 10.1177/1934578x1701200730
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structural Characterization and Neurotrophic Activity of Alkylamides fromZanthoxylum bungeanum

Abstract: Two new fatty acid amides, zanthoamides E (1) and F (2), were isolated from the pericarps of Zanthoxylum bungeanum. The structures of the two sanshool compounds were elucidated by analysis of spectroscopic data (IR, UV, HRESIMS, 1D and 2D NMR). All isolated compounds (1-9) were evaluated for nerve growth factor (NGF)-potentiating activity using PC-12 cells, and the results indicated that compound 8 (tetrahydrobungeanool) showed the strongest neurotrophic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Two new alkylamides, zanthoamides E (40) and F (41), along with seven known ones (ZP-amide A (42), ZP-amide B (43), ZP-amide C (44), ZP-amide D (45), Z P -a m i d e E (4 6 ) , t e t r ah y d r o b un g ea n o ol ( 4 7) , (2E,7E,9E)-N-(2-hydroxy-2-methylpropyl)-6,11-dioxo-2,7,9-dodecatrienamide (48)) were isolated from the pericarps of Z. bungeanum and structures determined by analysis of spectroscopic data (IR, UV, HRESIMS, 1D, and 2D NMR) (Wang et al 2017). Abdubakiev et al (2019) isolated sixteen known Nalkylamides from the dried fruits of P. longum.…”
Section: Extraction Isolation and Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Two new alkylamides, zanthoamides E (40) and F (41), along with seven known ones (ZP-amide A (42), ZP-amide B (43), ZP-amide C (44), ZP-amide D (45), Z P -a m i d e E (4 6 ) , t e t r ah y d r o b un g ea n o ol ( 4 7) , (2E,7E,9E)-N-(2-hydroxy-2-methylpropyl)-6,11-dioxo-2,7,9-dodecatrienamide (48)) were isolated from the pericarps of Z. bungeanum and structures determined by analysis of spectroscopic data (IR, UV, HRESIMS, 1D, and 2D NMR) (Wang et al 2017). Abdubakiev et al (2019) isolated sixteen known Nalkylamides from the dried fruits of P. longum.…”
Section: Extraction Isolation and Identificationmentioning
confidence: 99%
“…Z. bungeanum , popularly called “toothache tree” and widely distributed in China and Southeast Asian countries, is used as a condiment and in traditional medicine as anesthetic and analgesic for toothache and sore throats (Rong et al 2016 ). The pericarps from the fruits of Z. bungeanum are used in traditional medicine for the treatment of vomiting, toothache, stomachache, abdominal pain, and diarrhea (Wang et al 2017 ). Acmella oleracea (L.) R.K. Jansen, Asteraceae, is used in ethnomedicine to relieve toothache (Dallazen et al 2018 ).…”
Section: Ethnomedicinal Uses Of Alkylamide-containing Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [ 126 ] isolated nine alkylamides, including tetrahydrobungeanool, zanthoamides E and F, ZP-amides A-E and (2 E ,7 E ,9 E )- N -(2-hydroxy-2-methylpropyl)-6,11-dioxo-2,7,9-dodecatrienamide, from Z. bungeanum pericarps. In vitro neuritogenic test using rat pheochromocytoma PC-12 showed that the nine compounds enhanced neurite outgrowth, indicating that they have neuritogenic activity, without apparent cytotoxicity.…”
Section: Health-related Bioactive Properties Of Zanthoxylum Speciesmentioning
confidence: 99%